The Amalgamation of Internet of Things and Recommender Systems. Issue 1 (July 2021) - Sharma, Sheetal; Gupta, Kamali; Gupta, Deepali
Abstract: The Internet of Things (IoT) has upgraded the things and regular devices around to smart devices that can interact, share information and collaborate. With the plethora of IoT products, solutions, and workflows available online, the consumer finds it challenging to find the most suitable one. IoT, when integrated with the recommender system, can extend its features to the new space of innovation, usability, viability, and success. Various recommendation techniques can be employed to support users to get the best fit services, applications, sensors, products, and IoT workflows. This article will steer via the basic introduction of the IoT, its building blocks, hardware, software, applications, and its challenges. It analysed scientific articles indexed in the Scopus database with help of biblioshiny tool based on Rstudio software. The analysis is directed on 260 articles to figure out the trending amalgamation of Recommender System with the Internet of Things. Results point to fact that personalized recommendations for IoT-based applications are the most worked on topic by the authors.